Longitudinality and community orientation in the context of indigenous health - Esron Soares Carvalho Rocha; Rizioléia Marina Pinheiro Pina; Rosana Cristina Pereira Parente; Maria Luiza Pereira Garnelo; Rúbia Aparecida Lacerda (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to analyze, from healthcare professionals' perspectives, the longitudinality and community orientation in Primary Health Care, offered both in the Special Indigenous Health District and in the primary network that assists non-indigenous population in municipal health services in Upper Rio Negro region. Methods a cross-sectional study with 116 professionals, 87 (75%) of indigenous health, 29 (25%) of municipal services. Primary Care Assessment Tool, professional version, used by Upper Rio Negro for Social Sciences region. For association of variables, chi-square test and Kruskal-Wallis were used. Results longitudinality obtained an unsatisfactory score (6.4 and 6.5), as well as community orientation (6.1 and 5.6) for both services. Weaknesses refer to professional turnover, little knowledge about users' living conditions, precarious employment relationship. In indigenous health, satisfaction was higher when compared to municipal services. Conclusions: it is necessary to improve work management in health services, seeking to guarantee the quality of performance of professionals.